2014
DOI: 10.1186/preaccept-1479195265134573
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals tomato genes whose expression is induced specifically during effector-triggered immunity and identifies the Epk1 protein kinase which is required for the host response to three bacterial effector proteins

Abstract: Background: Plants have two related immune systems to defend themselves against pathogen attack. Initially, pattern-triggered immunity is activated upon recognition of microbe-associated molecular patterns by pattern recognition receptors. Pathogenic bacteria deliver effector proteins into the plant cell that interfere with this immune response and promote disease. However, some plants express resistance proteins that detect the presence of specific effectors leading to a robust defense response referred to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…Fni3) and UBC13-2 were shown previously to catalyze exclusively the unconventional, Lys-63-linked ubiquitination and to be required for immunityassociated PCD induced by Fen and several other ETI elicitors (Mural et al, 2013). More recently, two gene expression profiling studies of tomato immunity against Pst using high-throughput RNA sequencing identified multiple Flagellin-induced repressed by effectors genes and genes induced specifically during ETI, among which UBC12, UBC13, UBC13-2, UBC25, and UBC28 were found to be induced significantly during ETI, and UBC25 also was induced significantly in PTI (Rosli et al, 2013;Pombo et al, 2014). These findings not only corroborate the discovery that tomato UBC13 (Fni3) and UBC13-2 play an important role in ETI (Mural et al, 2013) but also suggest that tomato E2s other than the group III members, such as UBC25, also may play an important role in plant immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fni3) and UBC13-2 were shown previously to catalyze exclusively the unconventional, Lys-63-linked ubiquitination and to be required for immunityassociated PCD induced by Fen and several other ETI elicitors (Mural et al, 2013). More recently, two gene expression profiling studies of tomato immunity against Pst using high-throughput RNA sequencing identified multiple Flagellin-induced repressed by effectors genes and genes induced specifically during ETI, among which UBC12, UBC13, UBC13-2, UBC25, and UBC28 were found to be induced significantly during ETI, and UBC25 also was induced significantly in PTI (Rosli et al, 2013;Pombo et al, 2014). These findings not only corroborate the discovery that tomato UBC13 (Fni3) and UBC13-2 play an important role in ETI (Mural et al, 2013) but also suggest that tomato E2s other than the group III members, such as UBC25, also may play an important role in plant immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of UBC11, UBC12, UBC13, UBC13-2, UBC25, UBC28, UBC29, UBC39, and UBC40 in either PTI and/or ETI in this and previous studies warrants further investigation of them in plant immunity (Mural et al, 2013;Rosli et al, 2013;Pombo et al, 2014). Since the connections of these E2s with E3 ligases in plant immunity have not been established, screening for and characterization of E3 ligases that work with these E2s in PTI and/or ETI and subsequently pinpointing and characterizing the substrates they modify should be the next experiments in elucidating the roles of E2s in the plant immune system.…”
Section: Discussionmentioning
confidence: 99%
“…A VIGS forward screen in N. benthamiana for PTI genes revealed surprisingly few essential genes and no silver‐bullet candidates for the PTI‐protected state (Chakravarthy et al ., ). However, RNA‐seq transcription profiling aimed at distinguishing PTI and ETI responses of tomato to DC3000 derivatives revealed enrichment for genes associated with the phenylpropanoid pathway in the PTI‐specific set (Pombo et al ., ). Phenylpropanoid pathway genes were similarly found in a transcriptome study of PTI genes in tobacco (Szatmari et al ., ), and the N. benthamiana VIGS screen identified the CA4H gene which plays a role in phenylpropanoid biosynthesis (Chakravarthy et al ., ).…”
Section: Defence Subversion and Other Processes Promoting Pathogenesimentioning
confidence: 97%
“…NormFinder uses a model‐based approach allowing intra‐ and inter‐group comparisons of the obtained Ct values, and it provides a ranking of the candidate reference genes based on the estimated standard deviations. Recent studies have proposed different reference genes for expression studies during tomato ( Solanum lycopersicum ) development (Expósito‐Rodríguez, Borges, Borges‐Pérez, & Pérez, ) and tomato–pathogen interactions (Fradin et al., ; Müller et al., ; Pombo et al., ). Primer pairs for ten of these genes—four classical housekeeping genes, such as elongation factor EF1‐ α and ATPase (Expósito‐Rodríguez et al., ; Pombo et al., ), and six newly suggested ones (Müller et al., ; Pombo et al., )—were selected and evaluated in tomato–grey mould interaction.…”
Section: Introductionmentioning
confidence: 99%
“…tomato interaction. The pathogen–leaf infiltrations were performed on whole plants from which leaf samples were harvested at 3, 6, 9 and 12 hrs postinoculation (hpi) (Pombo et al., ). Primers amplifying importin β (primer set IMP‐β), PHD finger family protein (PHD), cytochrome c oxidase subunit (COX), polyribonucleotide 5′‐hydroxyl‐kinase (CLP1) and U6 snRNA‐associated Sm‐like protein LSm7 (LSM7) were used in a tomato (cv.…”
Section: Introductionmentioning
confidence: 99%